A postgraduate qualification in tuberculosis—Message in a bottle. (March 2020) - Tiberi, Simon; Zumla, Alimuddin; Raviglione, Mario; Lipman, Marc; Kon, Onn Min; Griffiths, Chris; Migliori, Giovanni Battista
Abstract: The TBCert is a distance-learning course, launched in 2019 and hosted by QMUL. The course is open to doctors, nurses, and public health workers who wish to subspecialize in TB. The course was established to elevate TB medicine to a subspecialty. We feel it is imperative to educate health practitioners from different sectors to deliver the most advanced level of care and control activities, standardisze training, reduce clinical variability, and instil best practice. The courses main objectives are to provide a relevant syllabus delivered through high quality teaching from world-class experts using an innovative interactive online platform. The curriculum is based on current internationally accepted (including WHO) guidelines and recommendations. Students are taught with pre-recorded lectures and regular live online webinar discussions delivered by experts in the field. Online discussion groups, one to one teaching-to-one teaching, and mentorship are organiszed to promote a shared as well as a tailored experience that helps students attain the learning outcomes and achieve their expectations.